THE IMPACT OF ENGLISH COMIC MEDIA ON EIGHTH-GRADERS’ READING MOTIVATION AND ABILITY AT SMPN 29 PADANG - Ifana Syahesti; Muhammad Al-Hafizh (Indonesian EFL Journal, 2026)
This study examines the effect of English comic media on eighth-grade students’ reading motivation and reading ability at SMPN 29 Padang. Comics were selected because their integration of visuals and text helps reduce cognitive load and increases student engagement compared to traditional text-based materials. This quantitative study employed a true experimental design with a post-test-only control group. Two classes selected through cluster random sampling participated in the research: VIII.1 (experimental, 31 students) and VIII.5 (control, 32 students). Students’ reading ability was assessed through a validated post-test, while reading motivation was measured using a questionnaire covering eight dimensions based on Guthrie & Wigfield’s framework: Grades-compliance, Involvement, Social Competition, Reading Work Avoidance, Curiosity, Recognition, and Efficacy. Independent Samples t-Test results revealed significant differences between groups for both reading ability (p < 0.05) and reading motivation (p < 0.05). The experimental group outperformed the control group, indicating that English comic media effectively enhances students’ reading comprehension and motivation. These findings highlight the potential of comics as engaging and pedagogically beneficial materials for EFL reading instruction.